Helicobacter pylori infection in systemic sclerosis: A systematic review and meta-analysis of observational studies - W. C. Yong (2019)
© COPYRIGHT CLINICAL AND EXPERIMENTAL RHEUMATOLOGY 2018. Objective: It has been proposed that Helicobacter pylori (H.pylori) infection causes several extra-gastrointestinal disorders. However, the role of H.pylori infection in the pathogenesis of systemic sclerosis (SSc) is still debatable. This meta-analysis is aimed at exploring the association between SSc and H.pylori infection. Methods: A comprehensive search of the MEDLINE and EMBASE databases was performed from inception through February 2018. The inclusion criterion was observational studies evaluating H.pylori infection in SSc. The pooled odds ratio (OR) of H.pylori infection and their 95% confidence interval (CI) were calculated using a random-effects meta-analysis to compare risk between SSc patients and healthy controls. The between-study heterogeneity of effect-size was quantified using the Q statistic and I 2 . Results: Data were extracted from 8 observational studies involving 1,446 subjects. The pooled results demonstrated an increased H.pylori infection in SSc compared with healthy controls (OR=2.10; 95% CI: 1.57-2.82, p-value<0.01, I 2 =13%). Subgroup analysis showed an increased risk of H.pylori infection measured with H.pylori ELI-SA test (OR=2.49; 95% CI: 1.82-3.40, p-value<0.01, I 2 =0%). Conclusion: Our study has shown that patients with SSc have an increased prior existence of H.pylori infection. This finding implies that the role of previous infection may cause an abnormal immunological cascade in the pathogenesis of SSc. Further studies that could elucidate the inflammatory response in the pathogenesis of SSc are warranted.